The Relationship between Family Support and Compliance with Cancer Patients Undergoing Chemotherapy - Della Oktavia Sari; Yulia Rizka; Yunisman Roni (CV. Rayyan Dwi Bharata, 2025)
Chemotherapy is one of the treatments for patients diagnosed with cancer. Patients undergoing chemotherapy must adhere to treatment in order to achieve success. Family support plays an important role in patient compliance in undergoing chemotherapy. The aim of the research was to determine the relationship between family support and cancer patient compliance in undergoing chemotherapy. This research uses a quantitative design with a cross-sectional approach. Respondents were selected using a purposive sampling method, totaling 85 respondents who met the inclusion criteria. The instrument used is a family support questionnaire which has been tested for validity and reliability. Patient medical record book to measure patient compliance. The analysis used is univariate and bivariate using the Kolomogrov-Smirnov alternative test because it does not meet the Chi-Square test requirements. Univariate analysis showed that the majority of respondents were in late adulthood (41-60) 58 (68.2%), female 62 (72.9%), primary school education 30 (35.3%), housewife occupation 39 (45.9), income <3,200 .00 62 (72.9%), married 77 (90.6%), ca mammae cancer type 42 (49.4%), stage III 72 (84.7%), good family support 67 (78.8%), obedient 68 (80.0%). The results of the Kolomogrov-Smirnov analysis p-value = 0.000<0.05. There is a significant relationship between family support and cancer patient compliance in undergoing chemotherapy.